2016
DOI: 10.1037/xhp0000193
|View full text |Cite
|
Sign up to set email alerts
|

Misperception of orthographic neighbors during silent and oral reading.

Abstract: The study examined whether words are misperceived during natural fluent reading and the extent to which contextual and lexical properties bias perception. Target words were pairs of orthographic neighbors that differed in frequency. Pretarget context was neutral (Experiment 1) or biased toward the higher frequency member of the pair (Experiments 2 and 3), and posttarget context was neutral, congruent, or incongruent. Critically, incongruent context was constructed so that it was congruent with the target's nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 30 publications
7
40
0
1
Order By: Relevance
“…Using eye-movement-contingent display changes to manipulate the visibility of text to the left of a fixation, so that it was either masked or re-readable after a regression, Schotter et al [27] showed that sentences with garden path constructions were understood more successfully when readers re-read text after a regression. Readers also appear to use regressions to correct word identification errors [28], and to fill in “missed” sentence and story parts that were viewed during episodes of mind wandering and attentional lapses [29].…”
Section: The Function Of Regressionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using eye-movement-contingent display changes to manipulate the visibility of text to the left of a fixation, so that it was either masked or re-readable after a regression, Schotter et al [27] showed that sentences with garden path constructions were understood more successfully when readers re-read text after a regression. Readers also appear to use regressions to correct word identification errors [28], and to fill in “missed” sentence and story parts that were viewed during episodes of mind wandering and attentional lapses [29].…”
Section: The Function Of Regressionsmentioning
confidence: 99%
“…Using a similar approach, we examined the rate of regressions that moved the eyes onto the source of a presumed processing difficulty [28]. The materials were constructed so that controlled target words would be the source of a processing difficulty in an incongruent condition but not in a congruent condition.…”
Section: The Function Of Regressionsmentioning
confidence: 99%
See 3 more Smart Citations